Design and optimisation of lysozyme protein purification process using non-thermal progressive freeze concentration technology - Rashid T.; Jusoh M.; Zakaria Z.Y.; Yahya N.; Ansar S.; Kiong T.S.; Sher F. (Elsevier B.V., 2025)
In this study, PFC system is investigated to improve the concentration and yield of lysozyme. The research focused on an attempt to thoroughly construct an ice crystallizer with measurable and optimized design parameters for an efficient lysozyme protein concentration procedure because the productivity of PFC is always an issue. A new Multiple Probe Cryo-Concentrator (MPCC) device was designed and successfully equipped with probes having a well-distributed cooled surface area for ice crystallization with proper internal cooling temperature control as well as a solution movement mechanism provided by a stirrer in the tank. The impact of different operating parameters is optimally investigated. Central Composite Design (CCD) is utilized to optimize PFC operating conditions and their response to partition constant (K-value) and solute yield. The results showed that a coolant temperature of -12 ?C, stirrer speed of 350 rpm, operation time of 40 min and initial concentration of 10 mg/mL gave the best K-value (0.132) and solute concentration yield (87.39 %). The design elements of the equipment are crucial in providing improved PFC performance. The study revealed that the PFC system designed and applied in this study can improve the lysozyme protein concentration as needed in the food and pharmaceutical industry. ? 2024 The Author(s)